Cold Acclimation of the Thermoacidophilic Red Alga Galdieria sulphuraria: Changes in Gene Expression and Involvement of Horizontally Acquired Genes. (27th December 2018) - Rossoni, Alessandro W; Schnknecht, Gerald; Lee, Hyun Jeong; Rupp, Ryan L; Flachbart, Samantha; Mettler-Altmann, Tabea; Weber, Andreas P M; Eisenhut, Marion
Abstract: Galdieria sulphuraria is a unicellular red alga that lives in hot, acidic, toxic metal-rich, volcanic environments, where few other organisms survive. Its genome harbors up to 5% of genes that were most likely acquired through horizontal gene transfer. These genes probably contributed to G.sulphuraria 's adaptation to its extreme habitats, resulting in today's polyextremophilic traits. Here, we applied RNA-sequencing to obtain insights into the acclimation of a thermophilic organism towards temperatures below its growth optimum and to study how horizontally acquired genes contribute to cold acclimation. A decrease in growth temperature from 42C/46C to 28C resulted in an upregulation of ribosome biosynthesis, while excreted proteins, probably components of the cell wall, were downregulated. Photosynthesis was suppressed at cold temperatures, and transcript abundances indicated that C-metabolism switched from gluconeogenesis to glycogen degradation. Folate cycle and S-adenosylmethionine cycle (one-carbon metabolism) were transcriptionally upregulated, probably to drive the biosynthesis of betaine. All these cold-induced changes in gene expression were reversible upon return to optimal growth temperature. Numerous genes acquired by horizontal gene transfer displayed temperature-dependent expression changes, indicating that these genes contributed to adaptive evolution in G.sulphuraria .